Impact of Website Quality and User Satisfaction on Consumer Loyalty in Lithuanian C2C E-Commerce Platforms - Ūsas Antanas; Jasinskas Edmundas; Štreimikienė Dalia (Management şi Marketing)
This study was commenced to understand the effect of consumer satisfaction and website quality on loyalty in the Consumer to Consumer (C2C) E-Commerce business. This study used a survey method with the questionnaire as an instrument to gather the data required. As many as 400 respondents participated in this study, whereas all data was collected from those living in Lithuania and have used this website before. All data was then further processed and analysed using SPSS software. Descriptive statistics and regression analyses was used to determine website quality and satisfaction impact for consumer loyalty. After analysing all the gathered data, it can be concluded that website quality, and satisfaction positively affect customer loyalty in the C2C e-commerce business.